‏أضواء على فتنة غرداية: الحقيقة المطموسة بين الخوارج وأهل السنة والجماعة ردا على حصة في قناة اقرأ وكلمة للأحمد الشهمه - صدقي, محمد بن ايوب (المؤلف, 2014)
Keywords: Conflits -- Mzab; Polémique wahhabite

Destroy a mosque they prayed in… imprison them, and beat them | هدم مسجد كانوا يصلون فيه…سجنهم وضربهم - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
This post comes from a handful of fatwas I ran across in the famous Miʿyār al-Muʿrib of the 15th-century North African scholar Aḥmad al-Wansharīsī (d.914/1508). It turns out that this amazing colle…
Keywords: Polémique wahhabite